Adolescent and adult first time mothers' health seeking practices during pregnancy and early motherhood in Wakiso district, central Uganda - Annika Johansson; Tumwesigye Nazarius M; Mirembe Florence; Atuyambe Lynn; Kirumira Edward K; Faxelid Elisabeth (BMC, 2008)
Abstract Background Maternal health services have a potentially critical role in the improvement of reproductive health. In order to get a better understanding of adolescent mothers'needs we compared health seeking practices of first time adolescent and adult mothers during pregnancy and early motherhood in Wakiso district, Uganda. Methods This was a cross-sectional study conducted between May and August, 2007 in Wakiso district. A total of 762 women (442 adolescents and 320 adult) were interviewed using a structured questionnaire. We calculated odds ratios with their 95% CI for antenatal and postnatal health care seeking, stigmatisation and violence experienced from parents comparing adolescents to adult first time mothers. STATA V.8 was used for data analysis. Results Adolescent mothers were significantly more disadvantaged in terms of health care seeking for reproductive health services and faced more challenges during pregnancy and early motherhood compared to adult mothers. Adolescent mothers were more likely to have dropped out of school due to pregnancy (OR = 3.61, 95% CI: 2.40-5.44), less likely to earn a salary (OR = 0.43, 95%CI: 0.24-0.76), and more likely to attend antenatal care visits less than four times compared to adult mothers (OR = 1.52, 95%CI: 1.12-2.07). Adolescents were also more likely to experience violence from parents (OR = 2.07, 95%CI: 1.39-3.08) and to be stigmatized by the community (CI = 1.58, 95%CI: 1.09-2.59). In early motherhood, adolescent mothers were less likely to seek for second and third vaccine doses for their infants [Polio2 (OR = 0.73, 95% CI: 0.55-0.98), Polio3 (OR = 0.70: 95% CI: 0.51-0.95), DPT2 (OR = 0.71, 95% CI: 0.53-0.96), DPT3 (OR = 0.68, 95% CI: 0.50-0.92)] compared to adult mothers. These results are compelling and call for urgent adolescent focused interventions. Conclusion Adolescents showed poorer health care seeking behaviour for themselves and their children, and experienced increased community stigmatization and violence, suggesting bigger challenges to the adolescent mothers in terms of social support. Adolescent friendly interventions such as pregnancy groups targeting to empower pregnant adolescents providing information on pregnancy, delivery and early childhood care need to be introduced and implemented.